Scientific writing skills activity: A strategy for empowering botanical literacy - Murni Sapta Sari; Ahmad Kamal Sudrajat; Zainudin bin Hassan (Universitas Negeri Jakarta, 2023)
Botanical literacy makes students more familiar with the potential of botany in their area, especially plants that are beneficial to their lives. Science Writing Task has been proven to be able to increase students' scientific literacy. However, there has been no study discussing the effect of Science Writing Skills on botanical literacy. This study aimed to determine the effect of the Science Writing Task in improving students' botanical literacy. This research uses a mix-methods design strategy with an embedded model. The research using a cluster random sampling technique. The research subjects were 84 students of the Department of Biology in the 2018/2019 academic year. The research conducted at the Plant Structure and Development course. Quantitative data analysis used the ANCOVA test. Qualitative data analysis used data reduction. The results showed differences in the botanical literacy scores of students who were taught learning without the Science Writing Task and learning with the Science Writing Task, where learning with the Science Writing Task had higher botanical literacy. Based on qualitative data, students' understanding of botanical literacy is getting better, this can be seen from students' answers during learning. This study concludes that the Science Writing Task affects improving student botanical literacy.